O estudo dos ângulos através da construção de pipas com alunos do 6º ano na escola municipal Genival Alves Cavalcante - SILVA, Ionaria Silva da (2022)
This work will address the issue of teaching and learning about the study of post pandemic angles, in higher elementary education for the 6th grade class at the municipal elementary school Genival Alves Cavalcante, located in Vila Forquilha PA 256 Municipality of Tomé-Açu –Pa. We tried to answer the questions: how to work on angle studies with students coming from a pandemic? What is the didactic resource to be used for teaching angles with 6th grade students who have been away from schools for two years? Therefore, it was thought to organize a didactic sequence of activities around the making of kites that focuses on the contents: identification, classification and characterization of angles, the same aims to present the contributions in the use of kites as a concrete and manipulable material in the teaching and learning of mathematics, specifically for angle teaching. So that students who have been away from school for almost two years can assimilate the study of angles without holding the student only in books. Altair Baldissera (2008), he also points out that “it is important that they build, while in training, geometric knowledge from a practical and also playful perspective, which can be a “gateway” to learning Geometry at school”. During development, a questionnaire will be applied to students, where the aim is to obtain data and analyze how teaching and learning angles are. And also analyze the use of textbooks on angle studies for students in the 6th grade of elementary school. The didactic resource to be explored in this work through the construction of kites is to give students the opportunity to explore and identify the properties about angles and also appropriating the specific vocabulary related to elementary geometric shapes. It is considered that the construction of kites will be, in this case, an efficient didactic resource for teaching angle studies in higher elementary education.